Media Informasi Tata Cara Pendaftaran Mahasiswa Baru Berbasis Video Pada Universitas Bina Insani - Arifin, Rita Wahyuni; Setio Bekti, Gilang Mukti (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The development of information and communication technology is currently growing very rapidly. With technological developments, major changes have also occurred in the field of education. Bina Insani University accepts many students every year. Of course, the large amount of public interest in the programs offered by Bina Insani University has had an impact on increasing the registration of prospective new students at Bina Insani University. Information regarding new student admissions is currently still through brochures, banners, marketing visits to SMA/K schools, and also through social media. This was done as an effort to increase the number of new student registrants, however information regarding registration procedures is still presented in text form. Of course, this still makes it difficult for registrants to understand the correct order or registration. To overcome this problem, interactive information is needed that explains the procedures or procedures for registering new students at Bina Insani University. Based on the background of this problem, interactive information media is needed in the form of videos that explain the procedures for registering new students at Bina Insani University. By using the Multimedia Development Life Cycle (MDLC) method. This video can be accessed via the link listed on the official Bina Insani University website. It is hoped that with this research, prospective new students at Bina Insani University will no longer have difficulty getting information about the procedures for registering new students at Bina Insani University.